THE CHILD EXPLOITATION IN LEWIS CAROLL’S ALICE’S ADVENTURES IN WONDERLAND (VIEWED FROM MARXIST THEORY) - Nureni Kakanegi; Fachmi Alhadar; Nurfani Nurfani (Elite : English and Literature Journal, 2018)
This research discusses the exploitation of children in the novel Alice’s Adventures in Wonderland by Lewis Carroll viewed from Marxist Theory. The research focused on the kinds of exploitation to the child labor and the after effects that happen in Industrial revolution. The method of this research is Descriptive Qualitative  to describe problems in the forms of narration and analysis. This research used Marxist Theory to help   understand the allusions, or satires in the primary data, then to match with the real condition in nineteenth century from the library research and internet search about the important events that related to Karl Marx’s theory about the social stratifications that  into the Bourgeois and Proletariat in the society then caused an exploitation towards child labor. The research finds that children in Domestic and Industrial sectors of Industrial Revolution are exploited by the dangerous working tasks, bad treatments, and worst conditions of work place. These aspects effects less education and health issues for the children.Keywords: Exploitation, Child Labor, Bourgeois, Proletariat, Industrial Revolution Abstrak          Penelitian ini membahas tentang eksploitasi anak di dalam novel Alice’s Adventures in Wonderland oleh Lewis Carroll yang dilihat dari Teori Marxis. Penelitian terfokus pada jenis-jenis eksploitasi terhadap pekerja anak dan efek yang terjadi pada Revolusi Industri. Penelitian ini menggunakan Metode Deskriptif Kualitatif untuk mendeskripsikan masalah-masalah dalam bentuk narasi dan analisis. Penelitian ini menggunakan teori Marxis untuk membantu memahami beberapa sindiran di dalam data primer, kemudian disesuaikan dengan situasi yang nyata di abad ke-19 berdasarkan pencarian pustaka dan internet tentang peristiwa-peristiwa penting yang berhubungan terhadap teori Karl Marx tentang stratifikasi sosial yang memisahkan antara kaum Borjuis dengan kaum Buruh pada masyarakat yang kemudian menyebabkan eksploitasi terhadap pekerja, terutama yang masih anak-anak. Dari penelitian ini didapatkan bahwa pekerja anak-anak di masa Revolusi Industri bekerja di dalam sektor Domestik dan sektor Industri telah terekploitasi dengan pengerjaan tugas yang berbahaya, perlakuan-perlakuan buruk, dan kondisi tempat kerja yang tidak baik. Aspek-aspek ini lalu memberikan efek atau akibat yang dibagi ke dalam jangka pendek, yakni kurangnya pendidikan, dan jangka panjang, yang terdapat masalah-masalah kesehatan terhadap pekerja anak.